Giovani musulmani tra pratiche religiose ed etica della cittadinanza - Giacalone, Fiorella (Antropologia Pubblica, 2024)
The article examines the social practices of young observant Muslims in the GMI. Their transnational dynamics are revealed, on a family and religious level, such as those relating to double loyalty (faith and constitution) as Italian citizens. The text makes clear the relationship, in their lives, between Islamic faith and Italian culture, as well as the importance of connecting ethics and religion through social and cultural practices as Italian citizens of the Islamic religion. Their narratives convey how the concepts of nationality and citizenship must find new expressions for their multiple identities.